(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The shift towards electric vehicles (EVs) represents a transformative opportunity for Africa, promising to reduce carbon emissions, improve urban air quality, and foster sustainable development. However, the pace and success of this revolution remain uncertain, influenced by the continent’s unique economic, infrastructural, and social contexts. This article critically examines the current state of the electric car revolution in Africa, assessing the challenges and opportunities inherent in adopting EV technologies across diverse African markets. By analyzing key factors such as energy infrastructure, affordability, government policies, and private sector involvement, the study highlights the complex interplay between technological readiness and socioeconomic realities. Special attention is given to countries like Nigeria, South Africa, and Kenya, where emerging EV initiatives showcase varying levels of progress and potential. The role of international partnerships, investment in renewable energy, and capacity building are identified as pivotal in accelerating the transition. Furthermore, the article explores who is best positioned to drive this revolution, weighing the influence of governments, multinational corporations, local entrepreneurs, and grassroots organizations. It is noticeable, that the transition to electric mobility faces significant hurdles, such as unreliable electricity grids, high initial costs, and limited charging infrastructure, innovative policy frameworks and growing environmental awareness offer hope for meaningful progress. Ultimately, this article argues that Africa’s electric car revolution will be a gradual, multifaceted process requiring coordinated efforts among public and private sectors, regional cooperation, and sustained investment. The findings provide a roadmap for stakeholders seeking to realize Africa’s clean mobility future within the next two decades.